Liver tissue fragments obtained from males are the most promising source of human hepatocytes for cell-based therapies - Flow cytometric analysis of albumin expression. - Karolina Ewa Zakrzewska; Anna Samluk; Agnieszka Wencel; Krzysztof Dudek; Dorota Genowefa Pijanowska; Krzysztof Dariusz Pluta (PLoS ONE)
Cell-based therapies that could provide an alternative treatment for the end-stage liver disease require an adequate source of functional hepatocytes. There is little scientific evidence for the influence of patient's age, sex, and chemotherapy on the cell isolation efficiency and metabolic activity of the harvested hepatocytes. The purpose of this study was to investigate whether hepatocytes derived from different sources display differential viability and biosynthetic capacity. Liver cells were isolated from 41 different human tissue specimens. Hepatocytes were labeled using specific antibodies and analyzed using flow cytometry. Multiparametric analysis of the acquired data revealed statistically significant differences between some studied groups of patients. Generally, populations of cells isolated from the male specimens had greater percentage of biosynthetically active hepatocytes than those from the female ones regardless of age and previous chemotherapy of the patient. Based on the albumin staining (and partially on the α-1-antitrypsin labeling) after donor liver exclusion (6 out of 41 samples), our results indicated that: 1. samples obtained from males gave a greater percentage of active hepatocytes than those from females (p = 0.034), and 2. specimens from the males after chemotherapy greater than those from the treated females (p = 0.032).